Sorting out striga with Sesbania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Striga hermonthica, or striga as it is commonly known, is a pernicious parasitic weed that affects millions of hectares of land in sub Saharan Africa and is becoming a major constraint to food production on the African continent. Striga attacks a...